Structure-function relationship of ASH1L and histone H3K36 and H3K4 methylation - Kendra R. Vann; Rajal Sharma; Chih-Chao Hsu; Maeva Devoucoux; Adam H. Tencer; Lei Zeng; Kevin Lin; Li Zhu; Qin Li; Catherine Lachance; Ruben Rosas Ospina; Qiong Tong; et al. (Nature Communications)
Abstract The histone H3K36-specific methyltransferase ASH1L plays a critical role in development and is frequently dysregulated in human diseases, particularly cancer. Here, we report on the biological functions of the C-terminal region of ASH1L encompassing a bromodomain (ASH1LBD), a plant homeodomain (ASH1LPHD) finger, and a bromo-adjacent homology (ASH1LBAH) domain, structurally characterize these domains, describe their mechanisms of action, and explore functional crosstalk between them. We find that ASH1LPHD recognizes H3K4me2/3, whereas the neighboring ASH1LBD and ASH1LBAH have DNA binding activities. The DNA binding function of ASH1LBAH is a driving force for the association of ASH1L with the linker DNA in the nucleosome, and the large interface with ASH1LPHD stabilizes the ASH1LBAH fold, merging two domains into a single module. We show that ASH1L is involved in embryonic stem cell differentiation and co-localizes with H3K4me3 but not with H3K36me2 at transcription start sites of target genes and genome wide, and that the interaction of ASH1LPHD with H3K4me3 is inhibitory to the H3K36me2-specific catalytic activity of ASH1L. Our findings shed light on the mechanistic details by which the C-terminal domains of ASH1L associate with chromatin and regulate the enzymatic function of ASH1L.